Best practices in cloud-based Penetration Testing - Vasenius, Petrus (My University, 2022)
This thesis addresses and defines best practices in cloud-based penetration testing. The aim of this thesis is to give guidance for penetration testers how cloud-based penetration testing differs from traditional penetration testing and how certain aspects are limited compared to traditional penetration testing. In addition, this thesis gives adequate level of knowledge to reader what are the most important topics to consider when organisation is ordering a penetration test of their cloud-based systems or applications. The focus on this thesis is the three major cloud service providers (Microsoft Azure, Amazon AWS, and Google Cloud Platform). The purpose of this research is to fill the gap in scientific literature about guidance for cloud-based penetration testing for testers and organisations ordering penetration testing. This thesis contains both theoretical and empirical methods. The result of this thesis is focused collection of best practices for penetration tester, who is conducting penetration testing for cloud-based systems. The lists consist of topics focused on planning and execution of penetration testing activities.
Keywords: Cloud computing, Penetration testing, Cloud security